An Argus II Case Report - İrfan Perente; Gürkan Erdoğan; Muhittin Taşkapılı (Beyoglu Eye Journal, 2017)
The Argus II Retinal Prosthesis System (Second Sight Medical Products, Inc., Sylmar, CA, USA) is the first US Food and Drug Administration-approved retinal implant. It provides electrical stimulation of the retina and induces visual perception in individuals with low vision. It is used in patients with severe disease, such as retinitis pigmentosa (RP). Presently described is Argus II implantation in a patient with RP.